2023
DOI: 10.1136/jech-2022-219930
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns of childhood homelessness and early adolescent trajectories of internalising and externalising behaviour

Abstract: BackgroundChild homelessness has been associated with elevated mental health problems during early adolescence, a period of onset for psychiatric problems. Prior literature has relied on cross-sectional studies, limiting the understanding of temporality and trajectories of psychopathology. We extend prior literature by examining associations between child homelessness and internalising and externalising symptom trajectories in early adolescence, with consideration of timing and persistence of homelessness.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…This study does not mention whether the children were securely attached before homelessness, but the results show how the later onset of homelessness could turn a secure relationship into an insecure one. Kim et al (2023) studied how the timing of homelessness (early childhood [ages 0-5] and middle childhood [ages 6-8]) impacts children at 9 years old. They found that those who become homeless during middle childhood had the highest internalizing and externalizing scores at 9 years old when compared to the children who never became homeless.…”
Section: Developmental Stage As a Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…This study does not mention whether the children were securely attached before homelessness, but the results show how the later onset of homelessness could turn a secure relationship into an insecure one. Kim et al (2023) studied how the timing of homelessness (early childhood [ages 0-5] and middle childhood [ages 6-8]) impacts children at 9 years old. They found that those who become homeless during middle childhood had the highest internalizing and externalizing scores at 9 years old when compared to the children who never became homeless.…”
Section: Developmental Stage As a Moderatormentioning
confidence: 99%
“…Kim et al (2023) studied how the timing of homelessness (early childhood [ages 0–5] and middle childhood [ages 6–8]) impacts children at 9 years old. They found that those who become homeless during middle childhood had the highest internalizing and externalizing scores at 9 years old when compared to the children who never became homeless.…”
Section: Relevance Of Attachment Theory and Abc‐x Model To Homelessnessmentioning
confidence: 99%